AP English Language 2020 - Murphy, Barbara L.; Rankin, Estelle M. (New York : McGraw-Hill Education, 2020)
5 Steps to a 5: AP English Language Elite Student Edition 2020 introduces an effective 5-step study plan to help you build the skills, knowledge, and test-taking confidence you need to achieve a high score on the exam. This popular test prep guide matches the latest course syllabus and includes online help, six full-length practice tests (3 in the book and 3 online), detailed answers to each question, study tips, and important information on how the exam is scored. Because this guide is accessible in print and digital formats, you can study online, via your mobile device, straight from the book, or any combination of the three. With the "5 Minutes to a 5" section, you'll also get an extra AP curriculum activity for each school day to help reinforce the most important AP concepts. With only 5 minutes a day, you can dramatically increase your score on exam day!
Includes bibliographical pages :221-223
Keywords: English language -- Examinations -- Study guides; Advanced placement programs (Education) -- Examinations -- Study guides; College entrance achievement tests -- Study guides; Examinations; Study guides